Pengenalan Budi Daya Ikan dalam Ember untuk Kemandirian Pangan di Kampung Enam, Kota Tarakan - Miska Sanda Lembang; Rukisah Rukisah; Jimmy Cahyadi; Heppi Iromo; Azis Azis; Nuril Farizah; Muhammad Amien; Diana Maulianawati; Zainuddin Zainuddin; Awaludin Awaludin; Burhanuddin Ihsan; Ricky Febrinaldy; Kartina Kartina; Santria Santria; Patrice Sevania (Institut Pertanian Bogor, 2022)
The Covid-19 pandemic has had a major impact on society, such as job losses, rising staples, and economic hardship. Prices of food needs that continue to increase and are not affordable have resulted in food problems, one of which is protein. One of the high-quality protein is protein from fish. Fish as a fishery commodity that is relatively easy to cultivate on a large industrial scale and household scale for food self-sufficiency is catfish (Clarias sp). The purpose of this activity is to add insight and knowledge of the community about budikdamber for food self-sufficiency. The method of implementing community service activities in Kampung Six is carried out by counseling and training methods on Budikdamber. In this training activity, a bucket with 40 liters of water and 20 catfish seeds was used. Maintenance was carried out for 60 days with ad satiation feeding three times a day. Observations were made on growth, survival and water quality. The results of the activity found that 93% of the community partners had understood about Budikdamber. Budikdamber maintenance by partner communities gets an absolute weight growth value of catfish of 14 g, catfish survival value of 75%, and 1 bunch of kale per bucket. Based on the results of this activity, it is hoped that there will be the provision of special land for Budikdamber as an example for people who want to develop in their respective yards.